Early Childhood Creativity Through Loose Parts Learning Media: Evidences from Muslimat NU Matesih Playgroup - Maryanti, Ramdhani Novi; Utami, Tri (Seulanga : Jurnal Pendidikan Anak, 2025)
The lack of a comfortable playing space and freedom to explore hinders children's creativity, thus, it is crucial to have the proper learning media to support creativity development in early childhood. This study aims to enhance early childhood creativity through the implementation of loose parts learning media at Muslimat NU Matesih Playgroup. Loose parts are open-ended materials that can be arranged, assembled, combined, or separated freely and flexibly according to the child's imagination. The research employed Classroom Action Research (CAR) conducted collaboratively between the researcher and classroom teachers over several learning cycles. The results indicate that the use of loose parts, such as leaves, twigs, stones, and other natural materials, strongly stimulates children's imagination and expression. A joyful and participative learning atmosphere further supports the development of creativity, as reflected in children's ability to create unique and original works. By providing opportunities for free exploration and using easily accessible materials, children are trained from an early age to think creatively, independently, and innovatively.